Turkey Association of Railway Routes-Geomorphology - Cagliyan, Ayse; Bozkurt Yildiz, Aysel (Marmara Univ, 2013)
In today's world even more to protect the importance of transportation in the past has gained importance as it is. The road after first mode of transportation, heavy industry after the industrial revolution and the development of steam power ushered a new era in rail transport. Thus, larger loads of people and has become much easier and faster. Railways for the states and commercial, both military and political power, depending on the time they have been. For these reasons, the development of rail transport is given great importance and speed. Both the Republic of Turkey after the Ottoman period, as well as the construction of railroads has been a matter of priority. Railway routes in the world and in Turkey are influenced by geomorphological conditions. In this study, the formation of the railway network in Turkey and the country geomorphological conditions in the construction of railway lines were investigated.
Keywords: Geomorphology; railway; transportation; tilt; regions